Does connecting tobacco cessation intervention with tuberculosis care improve quality of life outcomes? - Awaisu, Ahmed; Nik Mohamed, Mohamad Haniki; Noordin, NM; Abd. Aziz, Noorizan; Syed Sulaiman, Syed Azhar; Ahmad Mahayiddin, Aziah; Muttalif, Abdul Razak (Elsevier Inc., 2011)
Objectives: The objective of this study was to document the impact of an integrated TB directly observed therapy short-course (DOTS) plus smoking cessation intervention (SCI) on HRQoL. Methods: This was a non-randomized controlled study (quasi experimental design) involving 120 TB patients who were current smokers at the time of TB diagnosis. Patients were assigned to either of two groups: conventional TB-DOTS plus smoking cessation intervention (SCIDOTS group) or conventional TB-DOTS only (DOTS group). The effects of the novel intervention on HRQoL were measured using EQ-5D questionnaire. Two-way repeated measure ANOVA was used to examine the effects. Results: When compared, participants who received the integrated intervention had a better HRQoL than those who received the conventional TB care. The SCIDOTS group had a significantly greater increase in EQ-5D utility score than the DOTS group during 6 months follow-up (mean± SD = 0.98 ± 0.08 vs. 0.91 ± 0.14, p = 0.006). Similarly, the mean scores for EQ-VAS showed a consistently similar trend as the EQ-5D indices, with the scores increasing over the course of TB treatment. Furthermore, for the EQ-VAS, there were significant main effects for group [F (1, 84) = 4.91, p = 0.029, η2 = 0.06], time [F (2, 168) = 139.50, p = <0.001, η2 = 0.62] and group x time interaction [F (2, 168) = 13.89, p = <0.001, η2 = 0.14]. Conclusions: This study provides evidence that an integrated TB-tobacco treatment strategy could potentially improve overall quality of life outcomes among TB patients who are smokers.